Sexually transmitted diphtheria. Issue 2 (23rd May 2012) - Berger, Anja; Lensing, Carmen; Konrad, Regina; Huber, Ingrid; Hogardt, Michael; Sing, Andreas
Abstract : Diphtheria is caused by diphtheria toxin-producing Corynebacterium species. While classical respiratory diphtheria is transmitted by droplets, cutaneous diphtheria often results from minor trauma. This report concerns the first case of sexually transmitted diphtheria in a patient with non-gonococcal urethritis after orogenital contact.